"I Lift My Lamp Beside the Golden Door" : A Comparison Between Scottish and Irish Immigrants in New York During the Nineteenth Century - Morness, Rebecca (My University, 2011)
Immigration has been a hot topic in the United States for hundreds of years. Immigrants have had a large part in building the United States into the country it is today and nearly every person has roots outside of America. This paper will include a comparison of two such immigrant groups, both of which have had a significant influence on the country. Scotland and Ireland are neighbors geographically and have had intertwining histories for hundreds of years. This close relationship did not hold when immigrants from both cultures sailed across the Atlantic in order to find new opportunities and a new home. There are many reasons for this break-up but the most important ones are religion, negative propaganda, and each group's nationalistic practices. This paper will discuss the difference in treatment between the two groups in New York, as well as analyze the reasons for the drastic distinctions. The purpose for doing so is to create a comparison between two cultures which come from rather similar backgrounds. There is a lot of information available about immigration for both Scottish and Irish-Americans; however, much of it is more narrative rather than comparative. This paper will serve as a bridge between the two narrative histories and offer a new point of discussion for those who are interested in the topic.
Keywords: Ethnic relations--New York (State)--History; Immigrants--New York (State)--History--19th century; Irish Americans--New York (State); Scottish Americans--New York (State)